PSYCHOANALYSIS IN CHRISTIAN GREY CHARACTER ON FIFTY SHADES OF GREY NOVEL BY E. L JAMES - Darise, Nurnaningsi; Usman, Happy Anastasia (ELLITE ( Journal of Education, Linguistics, Literature and Language Teaching), 2024)
This research aims to describe Christian Grey's personality in the novel “Fifty Shades of Grey” by E. L. James. This research uses qualitative descriptive method and Sigmund Freud's theoryin order to analyze Grey's psychological condition. The techniques of analyzing data are through three steps: data reduction, data display, and conclusion drawing. The researcher finds 20 data deal with Freud’s id, ego and superego. The results show that in id, there are 10 data. While in ego, there are 8 data. Whereas in superego, there are 2 data. The most dominant personality structure in his character is id. As the conclusions, Grey’s id shows that he has some strong sexual desires and aggressive urges. Grey’s ego shows that he tries to negotiate with Anastasia before having sexual activity. Whereas, Grey’s superego shows that he has a commitment as a principle in having a relationship with his partner. As the suggestions, this research is expected to provide readers with a deeper understanding to Christian Grey as the main character in the novel, to be as reference to the next researchers, and to inform people that the memory in the past may affect a person in his personality and his relationship with others.